Correction: Oral anticoagulant re-initiation following intracerebral hemorrhage in non-valvular atrial fibrillation: Global survey of the practices of neurologists, neurosurgeons and thrombosis experts - Xu, Yan; Shoamanesh, Ashkan; Schulman, Sam; Dowlatshahi, Dar; Al-Shahi Salman, Rustam; Moldovan, Ioana Doina; Wells, Philip Stephen; AlKherayf, Fahad (Université d'Ottawa | University of Ottawa, 2018)
[This corrects the article DOI: 10.1371/journal.pone.0191137.].